1966
DOI: 10.2135/cropsci1966.0011183x000600030012x
|View full text |Cite
|
Sign up to set email alerts
|

Thrips Injury to Upland Cotton (Gossypium hirsutum L.) Varieties1

Abstract: The purpose of this study was to obtain thrips injury data on Upland cotton varieties currently planted in the Southeast and to associate the effects of the injury with yield. Yield and thrips injury data were obtained on 16 varieties at Experiment, Georgia, in 1960, and thrips injury data on 12 varieties at Jackson, Georgia, in 1961. In 1960, a highly significant (P=.01) negative correlation (0.52) between yield and injury‐index was obtained. The linear regression showed a decrease of 392 pounds seed cotton p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Neonicotinoid seed treatments provide systemic protection of cotton seedlings during their period of vulnerability to thrips feeding injury, which extends from emergence until they have four to five true leaves. When left uncontrolled under cool growing conditions, direct feeding injury from thrips larvae can limit growth and delay fruiting and maturity . Although damaged plants may recover and suffer minimal yield loss when soil moisture is adequate, reduced root growth makes them vulnerable to water stress, exacerbating impacts on yield …”
Section: Introductionmentioning
confidence: 99%
“…Neonicotinoid seed treatments provide systemic protection of cotton seedlings during their period of vulnerability to thrips feeding injury, which extends from emergence until they have four to five true leaves. When left uncontrolled under cool growing conditions, direct feeding injury from thrips larvae can limit growth and delay fruiting and maturity . Although damaged plants may recover and suffer minimal yield loss when soil moisture is adequate, reduced root growth makes them vulnerable to water stress, exacerbating impacts on yield …”
Section: Introductionmentioning
confidence: 99%
“…() found that glandless cottons (low or no gossypol) generally had similar or lower damage from F. occidentalis than did glanded cottons. Other studies have identified resistance to thrips in some genotypes, such as the cultivars ‘Empire’ (Hawkins et al., ), Arkot 8710, and Arkot 8717 (Bourland & Benson, ), though the mechanism of resistance has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported significant differences in thrips abundance and/or thrips feeding damage ratings between Gossypium hirsutum L. genotypes (Ramey, 1962;Hawkins et al, 1966;Quisenberry & Rummel, 1979;Zareh, 1985;Leigh, 1995;Arif et al, 2006;Khan et al, 2014). Despite these findings, there are few, if any, commercial cultivars with high level resistance to thrips (e.g., Cook et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since their registration nearly two decades ago, neonicotinoid seed treatments (NSTs) have been one of the most important and effective tools for managing early‐season infestations of tobacco thrips ( Frankliniella fusca Hinds) on cotton in the mid‐south and southeastern USA . Adult F. fusca infest cotton seedlings early in the growing season, ovipositing into cotton leaves, and exposing the seedlings to damage from subsequent larval feeding . Frankliniella fusca larval feeding can lead to leaf damage, injure the meristem and disrupt apical dominance in the plant, reduce root development, and may reduce yield .…”
Section: Introductionmentioning
confidence: 99%